A 15-YEAR-OLD BOY WITH PROTRACTED VISION LOSS FROM ACUTE POSTERIOR MULTIFOCAL PLACOID PIGMENT EPITHELIOPATHY. Issue Volume 15:Issues 6(2021) (November 2021) - Sulewski, Michael E.; Kolomeyer, Anton M.; Saran, Bruce R.; Brucker, Alexander J.
Abstract : Purpose: To present an atypical case of acute posterior multifocal placoid pigment epitheliopathy in a 15 year old treated with immunosuppressive therapy. Methods: Interventional case report. Results: On initial presentation, the vision was 20/200 in the right eye and 20/300 in the left eye. The posterior poles of both eyes showed numerous creamy-white placoid lesions. Fundus autofluorescence demonstrated hypoautofluorescence lesions with hyperautofluorescence rims, while fluorescein angiography showed early blockage followed by late staining. These findings were consistent with a diagnosis of acute posterior multifocal placoid pigment epitheliopathy. Optical coherence tomography demonstrated outer retinal disruptions and thinning. Due to the severity of his disease, the patient was treated first with oral prednisone and later transitioned to mycophenolate mofetil by 2 months. His poor vision persisted beyond a 5-month follow-up visit despite fading of the lesions and reconstitution of the outer retinal layers and thickness on optical coherence tomography. By 8 months of follow-up, the visual acuity returned to 20/20 bilaterally without any further recurrences. Conclusion: Although most patients with acute posterior multifocal placoid pigment epitheliopathy have a relatively short course and recover vision quickly, the use of steroids and immunosuppression may be of benefit for those patients with severe and prolonged visual loss. Abstract : The authors present an unusual case of acute posterior multifocal placoid pigment epitheliopathy in a 15 year old with severely decreased vision persisting at 5 months before ultimately returning to 20/20. This case highlights the potential protracted course of the disease and possible role for immunosuppression.